2018
DOI: 10.20517/2394-5079.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant hepatic arterial infusion chemotherapy for resectable hepatocellular carcinomas

Abstract: Aim: To evaluate the effect of neoadjuvant hepatic arterial infusion chemotherapy (HAIC) on the survival of patients with resectable hepatocellular carcinoma (HCC). Methods: Between January 2003 and January 2014, 80 patients underwent hepatic resection for HCC. Of these patients, we evaluated 49 patients who met the following inclusion criteria: (1) preserved liver function (Child-Pugh A); (2) resectable HCC (≤ 3 nodules, regardless of the size); and (3) HCC with high-grade malignant potential. Among them, 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Another retrospective study showed that neoadjuvant HAIC reduced the risk of recurrence in patients at a high risk of hepatocellular carcinoma and improved patient survival rates. Compared with the control group, the 1-, 3-, and 5-year DFS rates (100%, 78.6%, and 78.6% vs 65.8%, 33.7%, and 26.6%, respectively, P = 0.003) and OS rate (100%, 100%, and 100% vs 91.7%, 77.8%, and 55.3%, respectively, P = 0.037) in the neoadjuvant HAIC group were significantly higher[ 21 ] (grade of evidence: 2B).…”
Section: Strategies For Conducting Neoadjuvant Therapymentioning
confidence: 99%
“…Another retrospective study showed that neoadjuvant HAIC reduced the risk of recurrence in patients at a high risk of hepatocellular carcinoma and improved patient survival rates. Compared with the control group, the 1-, 3-, and 5-year DFS rates (100%, 78.6%, and 78.6% vs 65.8%, 33.7%, and 26.6%, respectively, P = 0.003) and OS rate (100%, 100%, and 100% vs 91.7%, 77.8%, and 55.3%, respectively, P = 0.037) in the neoadjuvant HAIC group were significantly higher[ 21 ] (grade of evidence: 2B).…”
Section: Strategies For Conducting Neoadjuvant Therapymentioning
confidence: 99%
“…The use of TACE as a neoadjuvant treatment before liver resection is debated, because it may be useful to eradicate intrahepatic metastases and prevent tumor cell dissemination during surgery [Figure 4], but carries the risks of liver function impairment, delay in surgery and perihepatic adhesions rendering liver resection more difficult [83,84] . A meta-analysis [85] showed that the overall survival after liver resection was worse in the case of preoperative TACE, but the subgroup with complete tumor response to TACE had a benefit in disease-free survival after surgery because of reduced tumor recurrence rate. Although DSM-TACE has not yet been tested for this neoadjuvant indication, the significantly better patient outcome was obtained with hepatic artery infusion (HAI) [86] , which is based on the same principle of chemotherapeutic action.TACE has been successfully applied before thermal ablation to increase the HCC necrotic area in HCC nodules based on the ischemic effect of embolization [2,87] , but also in combination with external radiotherapy, proving effective in terms of increased tumor response and patient outcome due to the synergistic effect of chemo-radiotherapy [88] .…”
Section: Indications Of Tace In Mdtb-selected Hcc Patientsmentioning
confidence: 99%